Increasing the Brand Awareness of Panji Mas Shop with a Company Profile Video - Illona Mora Kartika (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Panji Mas shop is a business selling decorative and automotive paints in Singaraja, Bali. Most of its customers are men between the ages of 41 and 65 (low-middle-high income). However, due to the current re-generation of business owners, Panji Mas shop will also concentrate on expanding its target market to 18 to 40 years old. The main problem for the shop is that Singaraja people are still unfamiliar with it and its products (lack of brand awareness). The main cause is because of not using specific marketing strategies. Therefore, the writer chooses a company profile video shared on Facebook and Instagram as an ad based on Esp and Bie Production (2022). The company profile video will also highlight the shop's USPs, which are the wide range of automotive and decorative paints, mixing colors, and great services. As a result, it can help the shop increase its brand awareness.